KEDUDUKAN RISALAH LELANG SEBAGAI UPAYA HUKUM PENEGAKAN HAK-HAK KREDITUR DALAM PERJANJIAN KREDIT BANK - Widhya Sastra, I G N Agung; Putra Atmadja, Ida Bagus; Wiratni Darmadi, A. A. Sagung (Kertha Semaya : Journal Ilmu Hukum, 2013)
This paper departs from standing problem treatise auction for the rights of the creditor when the debtor defaults.This paper is intended to answer the question of how the position of the Minutes of Auction for the fulfillment of the rights of the bank as a creditor when the debtor defaults and how the force of law as evidence the minutes of the auction transitional land rights. In his discussion, accompanied by APHT credit agreement which is then used by the lender to carry out the auction for the collateral to satisfy creditors' rights. In addition it was found that the minutes of the auction is referred to as an authentic act in PMK 93/PMK.06/2010 numbers on Implementation Guidelines Auction did not meet the elements of an authentic act as stated in the Civil Code.Conclusion treatise auction is a testament to the creditors that the auction had been conducted according to the procedures and results of the auction has been used to satisfy creditors' rights and by Article 37 Paragraph (1) in conjunction with Article 41 paragraph (1) of Government Regulation No. 24 of 1997 on the Registration ground, can be used as the basis of the minutes of the auction registration of transfer of land rights, but the strength of proof is not perfect because it is not an authentic act but has the same legal force with PPAT deed.
Keywords: Minutes of the auction, authentic deed, the efforts of law, creditors' rights